The Influence of Semantics and Syntax on Sentence Repetitions in SLI Children - Jelaska (Babić), Zrinka (Array, 1995)
There are more preferable word-order, easier and more difficult words in sentences. SLI children differ from control group mostly in the percentage of successful repetitions of 10 test sentences, but they also differ in some strategies they use when faced with difficult sentences.